Bifidobacterium breve in Improving Cognition on Older Patients with Mild Cognitive Impairment: A Literature Review - Dwiastri Iris Sarwastuti (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
Mild Cognitive Impairment (MCI) is a transitional phase between normal cognitive aging and dementia, characterized by noticeable cognitive decline that is not severe enough to interfere with daily life. Recent studies suggest that probiotics, particularly Bifidobacterium breve, may play a role in enhancing cognitive function in older adults with MCI.This literature review synthesizes findings from multiple studies published between 2018 and 2024, focusing on the effects of Bifidobacterium breve supplementation on cognitive improvement.Seven articles were identified that addressed the impact of Bifidobacterium breve on cognitive functions in older adults with MCI. These studies utilized various methodologies, including randomized controlled trials and open-label studies, and consistently reported positive outcomes in cognitive performance.The results indicate that Bifidobacterium breve supplementation can enhance cognitive functions by modulating the gut microbiota, reducing inflammation, and promoting neuroprotective effects. These findings suggest a potential therapeutic avenue for managing cognitive decline in older adults.The evidence supports the hypothesis that Bifidobacterium breve may improve cognition in older patients with MCI, highlighting the need for further research to confirm these findings and explore the underlying mechanisms.